Comparison of interferometric light microscopy with nanoparticle tracking analysis for the study of extracellular vesicles and bacteriophages. Issue 2 (23rd February 2023) - Sausset, Romain; Krupova, Zuzana; Guédon, Eric; Peron, Sandrine; Grangier, Alice; Petit, Marie‐Agnès; De Sordi, Luisa; De Paepe, Marianne
Abstract: Research on extracellular vesicles (EVs) and bacteriophages (phages) has been steadily expanding over the past decades as many of their roles in medicine, biology, and ecosystems have been unveiled. Such interest has brought about the need for new tools to quantify and determine the sizes of these biological nanoparticles. A new device based on interferometric light microscopy (ILM), the Videodrop, was recently developed for this purpose. Here, we compared this new device to two nanoparticle tracking analysis (NTA) devices, the NanoSight and the ZetaView, for the analysis of EVs and phages. We used EVs isolated from bacteria, fecal samples, bovine milk and human cells, and phages of various sizes and shape, ranging from 30 to 120 nm of diameter. While NTA instruments correctly enumerated most phages, the Videodrop detected only the largest one, indicating a lower sensitivity threshold compared to the NTA devices. Nevertheless, the performance of the Videodrop compared favourably to that of the NTA devices for the determination of the concentration of eukaryotic EV samples. The NanoSight instrument provided the most precise size distributions but the Videodrop was by far the most time‐saving device, making it worthy of consideration for studies conducted on a large number of samples composed of nanoparticles larger than 90 nm.